Dendritic nanogel carrier and production method thereof

By using dendritic nanogel carriers with hydrophobic and hydrophilic chain segments, the stability and release control problems of antimicrobial peptide AMP are solved, and sustained release treatment for lung and skin infections are achieved, improving the treatment effect and reducing the Side effects.

CN112584867BActive Publication Date: 2024-12-13POLYMER FACTORY SWEDEN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980054465.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-08-13
Filing Date
2019-08-13
Publication Date
2024-12-13
Estimated Expiration
2039-08-13

AI Technical Summary

Technical Problem

In the prior art, the difficulty in stability and release control of antimicrobial peptide AMP leads to inefficiency in treating skin and lung infections, and it is difficult to target control the self-assembly and release of peptides, resulting in poor drug side effects and therapeutic effects.

Method used

Using dendritic nanogel carriers containing hydrophobic and hydrophilic segments, nanoparticles are formed by self-assembly and crosslinking, combined with allyl modification, to provide chemical stability, triggered release and controlled release characteristics, improving Bioavailability and local therapeutic effects of AMP.

Benefits of technology

Improve the chemical stability and release control of AMP, realize the sustained release treatment of lung and skin infections, reduce drug side effects, enhance treatment effect, and adjust the size of nanogels through hydrophilic chain segments, improving the Bioavailability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112584867B_ABST
    Figure CN112584867B_ABST
Patent Text Reader

Abstract

The present invention relates to nanogels of nanoparticles. The nanoparticles comprise a self-assembled dendrimer-containing polymer having at least one dendritic hydrophobic segment forming a core and at least one hydrophilic segment forming a shell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to nanogels or dendritic nanogel (DNG) carriers comprising dendritic hydrophobic segments and hydrophilic segments, characterized by being self-assembled hybrid materials with subsequent crosslinking between hydrophilic polyethylene glycol (PEG) and modified hydrophobic dendritic 2,2-bis(hydroxymethyl)propionic acid (bis-MPA), and characterized by the core being anionic or cationic, hydrophilic and / or hydrophobic. More specifically, the present invention relates to the use of said dendritic nanogels and corresponding preparations as therapeutic agents, for example for the prevention and / or treatment of skin infections, burn wounds and lung infections. Background Art

[0002] Dendritic molecules or highly branched molecules (e.g., dendrimers) are a class of well-defined nanostructured macromolecules with narrow polydispersity or even monodispersity and with multivalent surfaces suitable for further modification. Dendritic polymers have been extensively and continuously studied for biomedical applications, such as gene therapy, drug delivery, and bioimaging purposes. Dendritic polymers are multifunctional, allowing conjugation, complexation, and / or encapsulation of multifunctional moieties. Functional groups can be arranged at the periphery of the dendritic polymer, acting as highly accessible handles for the attachment of drugs or other functional groups. Since the functionality of drugs and ligands is diverse, it is necessary to explore the presentation of various functional groups on the surface of dendritic polymers. It is difficult to use different functional moieties (drugs or imaging agents) on a single dendritic polymer in a controlled manner because all peripheral groups of symmetrical dendritic polymers have the same reactivity. Suitable linkers or spacers are needed to react with the surface functional parts of the dendritic polymer to provide flexibility in attaching multiple moieties (e.g., drugs, imaging agents, or targeting agents).

[0003] In the prior art, it is well known to use dendritic molecules / dendrimers as carriers for drug delivery. It is also known that low molecular weight peptides can be attached to dendrimers to be carried to specific targets. Different types of "starting materials" can be used to generate dendritic structures, and a variety of "strategies" can be used to attach or encapsulate peptides and polypeptides.

[0004] The use of functional dendrimers based on aliphatic polyester building blocks to improve the efficiency of antimicrobial peptide AMPs (Feliu et al. 2011) has great potential because they are commercially available, biocompatible, highly homogeneous, and can be effectively tailored in composition, hydrophilicity, size, and geometry to effectively encapsulate peptides with various properties.

[0005] To date, most biomedical applications of dendrimers have focused on the delivery of small molecule drugs, primarily for oncology applications, such as the use of positively charged poly(amidoamine) PAMAM-based dendrimers to deliver the anthracyline antibiotic doxorubicin for breast cancer treatment. Dendrimers are now increasingly commercially available due to their potential as therapeutic agents in the field of nanomedicine (Rolland et al. 2009). To date, hyperbranched polymers have only been commercially developed in industrial large-scale applications. For example, hyperbranched BoltornTM based on 2,2-bis(hydroxymethyl)propionic acid (bis-MPA) facilitates the production of polyurethane car seats worldwide (Perstorp AB).

[0006] From a range of dendritic materials found in the literature, non-toxic and biocompatible bis-MPA based dendrimers belong to one of the most promising scaffolds for biological applications (Feliu et al. 2012, Carlmark et al. 2013).

[0007] Resistance to conventional antibiotics is a rapidly growing problem that, starting at the beginning of the last century, could render infections untreatable within a few years and return medical care to the pre-antibiotic era. Antimicrobial peptides (AMPs) have great potential as novel therapeutic agents against infectious diseases, as they are less likely to induce resistance due to their rapid and nonspecific mechanism of action. Functional delivery systems that can be applied directly to the site of infection will be developed to treat infections of the skin and burn wounds, as well as lung infections caused by methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa, and Mycobacterium tuberculosis (MTB).

[0008] Despite the extensive research and development efforts in the field of AMPs, only a few candidates have entered the late stages of clinical trials, and to date, no or only a few AMP-based products have reached the market (Pasupuleti et al. 2012). One of the main reasons is the challenges associated with the stability of the peptides during formulation and after administration, which leads to reduced efficiency (Eckert 2011). Proteolytic degradation and self-aggregation are typical problems observed for these compounds. In order to improve efficiency and stability, a variety of methods for modifying the peptide structure have been used. However, these challenges can be overcome by choosing novel formulation strategies. In this regard, nanotechnology offers a wide range of unexplored possibilities.

[0009] The unique properties of biodegradable nanostructured materials, including large surface area, flexible size range enabling transport across physiological barriers, ease of engineering and functionalization, possibility of targeting to different organs, and high loading capacity for active substances with multiple methods for controlling release kinetics, have led to a significant increase in interest in using nanoparticles in various drug delivery applications.

[0010] Patent application WO2011123591 (A1) provides a biocompatible nanoscale hydrogel particle suitable for injectable delivery of therapeutic agents for treating diseases or disease states and for bioimaging purposes. These nanoparticles, including crosslinked hydrogels of modified asymmetric PAMAM dendrimers and other polymers, are biodegradable and release therapeutic agents over a long period of time. An injectable hydrogel is also disclosed, comprising a crosslinked poly(amidoamine) dendrimer having at least two asymmetric orthogonal chemically selective peripheral ends, at least one of the asymmetric orthogonal ends being crosslinked to form a gel, and at least another of the asymmetric orthogonal ends being conjugated with a chemical agent. The patent application describes that the drug contained in the hydrogel can be a peptide, and further, describes that the hydrogel can be used for many different applications, such as for controlled drug release, cell delivery, tissue engineering, and as a molecularly engineered scaffold for wound coating. However, PAMAM is not biocompatible and the degradation products may be toxic.

[0011] Patent application US2012040431 (A1) discloses a dendrimer molecule comprising surface carboxylic acid groups. The application discloses a polymer loaded with a therapeutic agent, which is covalently attached to a low molecular weight peptide. The polymer can be usefully derivatized. The application claims a method for preparing a modified dendrimer, the method comprising the step of obtaining a dendrimer molecule comprising surface carboxylic acid groups. The patent application also discloses that the recognition portion is selected from the group consisting of: (i) a peptide comprising one or more hapten portions; (ii) folic acid; (iii) a targeting peptide; (iv) biotin; (v) an oligonucleotide; (vi) an anchor domain peptide; (vii) an antibody; and (viii) an antibody fragment.

[0012] Patent application WO2005009396 (A2) discloses the use of polypeptides for preventing and treating infections. However, it does not disclose an effective way to deliver the polypeptides.

[0013] Patent application WO2012109121 (A1) discloses an emulsion-based delivery system, wherein the emulsion comprises carbohydrate nanoparticles and bacteriocins are adsorbed on the surface of the nanoparticles. The system is made of nanoparticles comprising carbohydrate carriers and bacteriocins, wherein the bacteriocin comprises a peptide. In some embodiments, the patent application describes amphiphilic carbohydrate nanoparticles, phytoglycogen octenyl succinate (PG-OS), and PG-OS-stabilized emulsions used for delivering functional peptides with prolonged efficacy. The term "phytoglycogen or glycogen-based material" refers to dendritic (i.e., highly branched) α-D-glucan and carbohydrate nanoparticles. In other embodiments, the nanocarrier used is a negatively charged dendritic polysaccharide based on phytoglycogen, which adsorbs positively charged nisin molecules through electrostatic interactions.

[0014] like Figure 2 As shown, hybrids between dendritic structures and linear segments are well known in the prior art (so-called linear dendritic hybrids). The size of the dendritic part can be varied by growing different generations, i.e. G1, G2, G3, etc., each of which is based on a number of monomers. The linear part can also be varied by changing the chain length, so that the molecular weight varies (2 kDa, 5 kDa, 10 kDa, 20 kDa, etc.). Due to its amphiphilic nature, the structure can self-assemble in different ways depending on the solvent, temperature, drying method, etc.

[0015] An object of the present invention is to provide a biocompatible carrier that can be modified to encapsulate anionic, cationic, hydrophilic or hydrophobic materials. The carrier protects the encapsulated peptide from chemical and enzymatic degradation. Another object of the present invention is to avoid peptide self-assembly, and target and control the release of active peptides. The present invention provides a single or substantially single nanogel with a low polydispersity index (PDI).

[0016] Thus, the present invention provides nanostructured materials, more specifically nanogels suitable for releasing AMP, characterized in that they provide:

[0017] 1) Improved chemical stability. Deamidation is a common problem in the regulation and functionality of AMPs. It is believed that incorporation of AMPs into the present nanogels can reduce deamidation to varying degrees.

[0018] 2) Triggered release. The present nanogels are capable of triggered release of peptides. For example, this can be used to respond to bacterial enzymes that are present in high concentrations in areas of infection / infection.

[0019] 3) Controlled release. For certain infectious conditions, both for pulmonary and skin infections, sustained release formulations of AMPs may be of interest. Although AMPs have rapid bactericidal effects, sustained release of AMPs will be associated with reduced dosing frequency. In addition, sustained release during pulmonary administration will enable larger doses without causing toxicity due to relatively high peptide concentrations in lung fluid during administration of the AMP formulation.

[0020] Controlled drug release is essential for the treatment of many diseases. For cancer treatment, controlled drug release can not only reduce the adverse side effects caused by drugs, but also increase the local drug concentration in the tumor area and improve the therapeutic effect.

[0021] 4) Improved functionality. The present nanogels can be used to induce flexible functionality in formulations, such as absorbing excess fluid in wounds, having bioadhesive properties to increase local bioavailability, and improving skin hydration during topical application.

[0022] 5) The size of the nanogels can be easily controlled and adjusted by the length of the hydrophilic segments.

[0023] Furthermore, the present invention provides a simple and inexpensive method for preparing nanogels that can be used as drug carriers. Summary of the invention

[0024] In view of the above, the present invention relates to a nanogel and a method for preparing the nanogel. The nanogel according to the present invention comprises a polymer having a hydrophobic segment and a hydrophilic segment: wherein the hydrophilic segment is or comprises a polyethylene glycol (PEG) molecule, and the hydrophobic segment is a modified dendritic 2,2-bis(hydroxymethyl)propionic acid (bis-MPA) molecule, wherein the hydrophobic segment is modified with an allyl group.

[0025] In a first aspect, the present invention relates to a nanogel according to claim 1 .

[0026] In a second aspect, the present invention relates to a pharmaceutical composition comprising a nanogel according to the present invention for topical drug delivery.

[0027] In a third aspect, the present invention relates to a pharmaceutical composition comprising a nanogel according to the present invention for use in treating an infection selected from the group consisting of skin infections, burn wounds and lung infections.

[0028] In a fourth aspect, the present invention relates to a method for preparing a nanogel according to the present invention, wherein the method comprises the following steps:

[0029] - Produce hydrophobic segments and linear hydrophilic segments;

[0030] -Self-assembly of hydrophobic segments and linear hydrophilic segments into hybrid dendritic material scaffolds in the form of self-assembled core-shell nanoparticles;

[0031] - Cross-linking of the nanoscale assembled scaffolds on available allyl groups to obtain nanogels;

[0032] - Optionally post-functionalizing the nanogel to introduce desired functionality, such as anionic, cationic or hydrophobic moieties.

[0033] In a fifth aspect, the present invention relates to an aqueous composition comprising the nanogel according to the present invention, wherein the aqueous composition comprises 0.1-99.9 wt. % of the nanogel.

[0034] In a sixth aspect, the present invention relates to a nanogel comprising individual and / or interconnected nanoparticles having a core and a shell.

[0035] wherein the nanoparticle comprises a self-assembled dendrimer-containing polymer having at least one dendritic hydrophobic segment forming a core and at least one hydrophilic segment forming a shell;

[0036] wherein the hydrophilic segment is or comprises polyethylene glycol (PEG), and the hydrophobic segment is a dendritic 2,2-bis(hydroxymethyl)propionic acid (bis-MPA) molecule modified with allyl groups;

[0037] wherein the core of the nanoparticle is anionic, cationic, hydrophilic and / or hydrophobic; and wherein the hydrophobic segments are cross-linked by the allyl groups.

[0038] In the present invention, the core of the dendritic nanogel carrier is anionic, cationic, hydrophilic and / or hydrophobic. Depending on the core charge, it can load anionic drugs, cationic drugs or hydrophobic drugs.

[0039] In a preferred embodiment of the present invention, the active substance delivered is AMP.

[0040] The present invention also provides a formulation comprising a dendritic nanogel carrier delivered in the form of a topical spray, gel, or pulmonary aerosol.

[0041] Unless stated otherwise, all embodiments disclosed herein relate to all aspects of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The present invention will become better understood, and other advantages of the present invention will be readily appreciated, by referring to the following detailed description when considered in conjunction with the accompanying drawings, in which:

[0043] Figure 1A cross-linked biodegradable dendritic nanogel with an anionic internal structure is shown.

[0044] Figure 2 Shown is a synthetic material composed of linear polyethylene glycol (PEG) and dendritic 2,2-bis(hydroxymethyl)propionic acid (bis-MPA) with terminal allyl groups.

[0045] Figure 3 Data on the formation of structures evaluated by DNG are shown.

[0046] Figure 4 shows the self-assembly formation process: a) dialysis, b) thin film absorption. Each figure graphically summarizes the principle of the method.

[0047] Figure 5 shows the self-assembly formation process: a) solvent exchange, b) microdispersion. Each figure graphically summarizes the principle of the method.

[0048] Figure 6 shows a DLS concentration study of DLDhb87 / 13 and LD87 / 13: a) hydrodynamic diameter plotted against concentration, b) 100-peak area versus concentration defines the percentage of aggregates in the system.

[0049] Figure 7 Shown are DLS concentration studies of DLDhb87 / 13: a) PDI versus concentration, b) DLS traces at all measured concentrations.

[0050] Figure 8 The number of moles of amine and the number of moles of crosslinks are shown for each DNG formulation.

[0051] Fig. 9 The conversion percentage of allyl groups through self-assembly, cross-linking, and functionalization of DNG2 is shown.

[0052] Fig.10 For freeze-drying of the allyl-specific region of DNG2 1 H-NMR magnified image (right).

[0053] Fig.11 Shown is the size of DNG2 measured by DLS as a function of pH.

[0054] Fig.12 Shown are the size and PDI of DNGs recorded using DLS in PBS at room temperature.

[0055] Fig.13 Mitochondrial function on human dermal fibroblasts (HDF) as determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) over an incubation time of 72 hours is shown. DMSO 10% by volume was used as a positive control.

[0056] Fig.14 Shown are the dendritic nanogel size (a) and zeta potential (b) determined by DLS at different peptide loadings in μM.

[0057] Fig.15 DNGs with different sizes formed from DLDs with PEGs of different lengths. In all cases, the ratio of crosslinking:functional groups was kept at 3:5.

[0058] Fig.16 It is disclosed that the nanogels according to the present invention maintain or even improve the efficacy of DOX on a panel of cancer cells. The AlamarBlue assay was used to evaluate the cytotoxicity induced by free DOX and DOX-DNG on a panel of cancer cell lines at 72 hours of incubation.

[0059] Fig.17 Colocalization study on 3D spheroid model. a, b) Colocalization study of DOX-DNG3-NH2 on 3D PANC1 spheroids. DOX signal is represented by red fluorescence. Green fluorescence indicates (in a) calcein-AM labeled living cells or (in b) lysoTracker DND-26 labeled lysosomes in the cytoplasm; nuclei are stained with Hoechst 33342 and displayed as blue signals. c) Colocalization study of Pacific Blue labeled DNG-NH2 (DNGNH-PB) on 3D PANC1 spheroids. Blue fluorescence indicates DNG-NH-PB, and green fluorescence indicates calcein-AM labeled living cells. Scale bar = 100 μm. DETAILED DESCRIPTION

[0060] With reference to the cited figures, a description of the nanogel or dendritic nanogel carrier and the method for preparing the same according to the present invention is provided below.

[0061] The structure of the nanogel comprises a dendrimer-containing polymer comprising hydrophobic dendritic segments and preferably also linear hydrophilic segments. The dendritic segments and linear segments undergo a self-assembly mechanism and then undergo covalent crosslinking (interconnection) to produce a nanogel. The nanogel may contain water.

[0062] The present dendritic nanogel (DNG) is formed by forming a self-assembled core-shell nanoparticle (NP) through a self-assembly process of a dendrimer-containing polymer, which is then cross-linked to fix the structure. The nanogel can be post-functionalized to introduce desired functionality, such as anionic, cationic, hydrophilic or hydrophobic moieties, Figure 1According to the invention, the dendrimer-containing polymer is a hybrid material comprising a hydrophilic region of polyethylene glycol (PEG) and a modified hydrophobic region of dendritic 2,2-bis(hydroxymethyl)propionic acid (bis-MPA). The modification of the hydrophobic region is carried out by introducing one or more allyl groups on the bis-MPA. The PEG may have a molecular weight of 1,000 g / mol to 20,000 g / mol, for example 2,000 g / mol or more, or 5,000 g / mol or more, but 15,000 g / mol or less, or 10,000 g / mol or less. The PEG is preferably linear. The bis-MPA is preferably directly bonded to the PEG via an ester.

[0063] The inventors have found that the size of the nanoparticles or nanogels can be adapted or controlled by the length of the hydrophilic segments. For example, when a PEG having a molecular weight of 2,000 g / mol is used, an average size (Z average, ISO 22412) of 24 nm is obtained, while PEG of 6,000 g / mol and 10,000 g / mol produce Z averages (ISO 22412) of 122 nm and 150 nm, respectively. Fig.15 This is interesting because the body absorbs smaller particles much faster than larger particles (which still circulate in the body). This allows the uptake and release rates of the drug to be adjusted.

[0064] Three different scaffold architectures can be used to produce the above hybrid materials or polymers containing dendrimers, e.g. Figure 2 Shown: linear dendritic (LD), dendritic linear dendritic (DLD), dendritic linear dendritic hyperbranched (DLDhb) hybrids; wherein the linear polyethylene glycol (PEG) blocks can have two different lengths. DLDhb is characterized in that the hyperbranched scaffold is not structurally perfect compared to LD and DLD. The degree of branching (DB) is usually used to quantify the closeness of the hyperbranched structure to the dendritic structure. DB is defined as the ratio of perfect branches to the sum of all branches. The degree of branching is calculated using the Fréchet equation.

[0065] Quantification of terminal (T), linear (L), and dendritic (D) branching was performed using quantitative carbon NMR.

[0066] The degree of branching (DB) was calculated by Equation 2 using the integration of the characteristic signals of a specific monomer unit.

[0067]

[0068] Perfect dendritic structure DB = 1

[0069] Hyperbranching <1

[0070] Preferably, DB is less than 1, ie the dendritic part is hyperbranched, as it leads to better nanogels compared to perfect dendritic structures where the nanogels are monomorphic or essentially monomorphic (monomodal or narrow size distribution) with low PDI.

[0071] The hybrid material is characterized in that the relative percentages of hydrophilic and hydrophobic regions are different, as follows Figure 3 shown.

[0072] The step of self-assembly of dendritic hybrid materials into scaffolds can be achieved using four different methods known in the literature, as shown in Figures 4 and 5.

[0073] In a preferred implementation of the present invention, a thin film absorption method is used for the self-assembly step of the dendritic hybrid material, such as Figure 4b As shown. Compared with other methods of the prior art (Figures 4 and 5), the thin film absorption method is characterized by excellent self-assembly results, ease of use and convenient scalability. The method includes dissolving the polymer containing dendrons together with a UV initiator and a cross-linking agent in a suitable solvent such as dichloromethane (DCM) in a suitable container, and then slowly evaporating the solvent while twisting the container to coat a thin layer of polymer film on the side of the container. Then add an appropriate amount of water to disperse the polymer containing dendrons, forcing it to surround the hydrophobic cross-linker and initiator together with the hydrophilic part of the molecule for water, so that self-assembled core-shell nanoparticles are formed. The solution containing the self-assembled NP construct is then exposed to ultraviolet light, resulting in free radical cross-linking in the core, thereby fixing the structure and thus preventing decomposition.

[0074] Functionalization inside the NP construct can be performed by adding an excess of the desired functionalizing agent and a UV-initiator dissolved in water and exposing the mixture to UV radiation again. Dialysis against THF for 1 hour can then be used, followed by water purification using milli-Q water for 24 hours.

[0075] The self-assembly of polymers containing dendrimers exhibits the best performance when the relative molecular weight percentage (wt%) of the hydrophilic segments is 70-90 wt% and the relative molecular weight percentage of the hydrophobic segments is 10-30 wt%. This means that, for example, 70-90% of the total molecular weight of a linear dendrimer can be hydrophilic segments, such as PEG, and 10-30% can be hydrophobic segments, such as bis-MPA and peripheral groups.

[0076] In a preferred embodiment, excellent performance was obtained when the hydrophilicity ratio was 87 wt % and the hydrophobicity ratio was 13 wt % in terms of self-assembly using a thin film absorption method without cross-linking and functionalization. Therefore, different types of scaffolds can be prepared using the preferred hydrophobicity to hydrophilicity ratio, for example: LD87 / 13, DLD87 / 13, DLDhb87 / 13.

[0077] Surprisingly, the DLDhb87 / 13 scaffold showed excellent control over the self-assembled adducts, as shown in Figure 6, where the size of the constructs and the amount of aggregates were plotted relative to the corresponding scaffold and concentration. It was shown that the hyperbranched DLDhb87 / 13 material provided more controlled and defined NPs compared to other scaffolds with the same hydrophobicity to hydrophilicity ratio. Figure 6b In the figure, it is shown that the LD87 / 13 scaffold provides more aggregates, while the DLDhb87 / 13 scaffold provides more control over the self-assembled constructs. In terms of size, regarding nanogels or self-assembly, the LD87 / 13 is smaller than the DLDhb87 / 13 system, with diameter sizes as low as 50 nm, while the larger DLDhb87 / 13 system can provide sizes of 180-300 nm ( Figure 6a ).

[0078] Different PEG lengths and generations of dendrimers can be used for the formation of DNG. In a preferred embodiment, the dendritic segments are of the second generation (G2) or the third generation (G3). In a more preferred embodiment, the molecular weight of PEG is 2000-10000 g / mol and the dendritic segments are G2. In another more preferred embodiment, the molecular weight of PEG is 10000-20000 g / mol and the dendritic segments are G3. These embodiments result in nanogels that are monomorphic or substantially monomorphic (single peak or narrow size distribution) and have low PDI, e.g., 0.3 or lower, preferably 0.1 or lower, Figure 7 .

[0079] In one embodiment, the size distribution of the nanogels is substantially monomorphic or monomorphic, Figure 7 b. In another embodiment, the polydispersity index (PDI) of the nanogel is 0.3 or less, preferably 0.25 or less, or more preferably 0.20 or less, or even more preferably 0.1 or less.

[0080] The cross-linking rate in the nanogel may be 15-65 mol%, i.e., 15-65 mol% of allyl groups are used in the cross-linking. In a preferred embodiment, the cross-linking rate is 30-65 mol%, more preferably 50-60 mol%.

[0081] exist Figure 7The optimal concentration for NP formation is shown in , where the concentration is plotted against the dispersion index. Figure 7 As shown in the DLS trace in b, the lowest PDI, i.e. the narrowest size distribution and the most uniform NP, is obtained at a concentration of 5 mg / ml. At a concentration of 10 mg / ml, a small amount of nanogel aggregates are seen in the intensity trace, and aggregates are not seen in other cases for any concentration. In a preferred embodiment, the concentration is 3-6 mg / ml, more preferably 5 mg / ml. In a preferred embodiment, the pharmaceutical composition according to the present invention comprises 3-6 mg / ml or more preferably 5 mg / ml of nanogel.

[0082] The formation of dendritic nanogels by the cross-linking step of the nanoscale assembled scaffold provided a shrinkage from 295 nm to 220 nm (measured by DLS and TEM), which may be due to the shrinkage of the covalent bonds formed in the DNG. Cross-linking increased the stability, with the current date exceeding 300 days. The addition of THF and acetone in the cross-linked system did not cause the decomposition of the cross-linked system, while it caused complete decomposition in the non-cross-linked system, also indicating the formation of cross-links.

[0083] The cross-linking step can be performed at different percentages of available allyl groups, for example 15 mol% to 65 mol%. In a preferred embodiment of the invention, cross-linking is produced at the following percentages of available allyl groups: 18.25 mol%; 25.00 mol%; 31.25 mol%; 37.50 mol%; 62.50 mol%. Figure 8 A graphical representation of the degree of crosslinking and the molar amount of anionic moieties produced can be seen in . The gels are abbreviated dendritic nanogels (DNGs) and are numbered 1 to 5. In Table 1 the crosslinking rates for different DNGs can be seen.

[0084] Table 1 Cross-linking rate of DNG

[0085]

[0086] Crosslinking can be achieved using thiol chemistry that forms sulfide bonds or sulfide bridges. Crosslinking can be performed using mercaptopropionic acid or cysteamine with difunctional thiols or trifunctional thiols. Crosslinking can produce thioether bonds.

[0087] The allyl group can be any suitable C3 or longer alkyl group containing unsaturation. In one embodiment, the allyl group is a C3 to C6 group (-CH2-CH=CH2 to -(CH2)4-CH=CH2). In another embodiment, the allyl group is a C5 group (-(CH2)3-CH=CH2). The C5 group can be obtained by modification using 4-pentenoic acid. The longer chain length in the allyl group increases the hydrophobicity in the hydrophobic segment.

[0088] DNG has many advantages as a carrier, and large batches can be produced with a predetermined degree of cross-linking. Smaller batches can then be functionalized to display the properties of anionic cores, cationic cores, and hydrophobic cores. Covalent attachment in the core of fluorescent dyes combined with the aforementioned core features is also feasible. Various degrees of anionic moieties, cationic moieties, hydrophobic moieties, or moieties can be used to change the core properties to best suit the target cargo. In other respects, each batch is identical because the "naked" cross-linked scaffold comes from the same batch. Any thiol functional moiety can potentially be used to provide functionality or properties to the core, and any thiol molecule with multiple thiols equal to or greater than three can be used as a cross-linking agent. Fluorescent tags with thiol functionality can be incorporated into the core to provide traceability of the scaffold. The modular nature of DNG and its great possibility for modifying the core properties provide the possibility of customizing the system to carry or encapsulate a variety of cargoes, such as: cationic molecules or anionic molecules, such as cationic drug loading, anionic drug loading, hydrophobic or hydrophilic drug loading.

[0089] Encapsulation of cationic substances

[0090] Among them, the nanogel encapsulates the cargo as a cationic drug, so DNG was modified to show anionic properties in the core through the thiol-ene chemistry of appropriately cross-linked DNG and mercaptopropionic acid.

[0091] The cargo includes cationic peptides, cationic proteins, cationic antigens and cationic synthetic molecules, such as doxorubicin.

[0092] The loading of the peptide is done by taking into account the charge of the peptide and the charge of DNG. An amount of peptide having a total charge equal to or lower than the charge of DNG can be loaded into the system.

[0093] In a preferred embodiment, the antimicrobial peptide loaded onto the carrier is DPK-060, which is used to treat skin and soft tissue infections (SSTIs).

[0094] Higher peptide concentrations showed more pronounced aggregation compared to lower peptide concentrations. Interestingly, no significant change in the z potential was observed upon loading with DPK-060, suggesting that the gel structure contains charged cores screened from the surrounding environment by the linear PEG structure.

[0095] In another preferred embodiment, the antimicrobial peptide loaded onto the carrier is LL-37, which is an AMP widely used against a variety of bacteria and other pathogens (fungi, viruses).

[0096] The effects of nanosized AMPs, which are cationic, were evaluated using state-of-the-art in vitro and in vivo models.

[0097] Encapsulation of anionic substances The loaded substance is anionic drug, so DNG is modified to show cationic properties in the core by functionalization with cysteamine or its similar molecules.

[0098] The cargo includes SI-RNA, anionic peptides, anionic proteins, anionic antigens and anionic synthetic molecules, such as diclofenac, salicylic acid and ibuprofenic acid.

[0099] The loading is done by taking into account the drug charge and the DNG charge. An amount of drug having a total charge equal to or lower than the DNG charge can be loaded into the system.

[0100] Encapsulation of hydrophobic substances In the case where the cargo is a hydrophobic drug, DNG can be used without modification since the residual allyl groups not used for cross-linking and the dendritic blocks are hydrophobic. If a more hydrophobic nature is desired, the core can be functionalized, for example using hexanethiol.

[0101] The cargoes included doxorubicin, cisplatin, gemcitabine, erlotinib, fluorouracil, mitoxantrone, irinotecan, idarubicin, triptolide, paclitaxel, and many other drugs that are hydrophobic in nature.

[0102] The loading is performed by dissolving the hydrophobic drug together with the lyophilized DNG in a suitable solvent. Water or buffer is then added. The organic solvent is then completely evaporated and the excess drug can be purified by cassette dialysis.

[0103] In a preferred embodiment, the loaded hydrophobic drug is doxorubicin. Fig.14 The release of the drug over time is shown for four samples: free DOX, DNG1, DNG2 and DNG 5. A slow release profile can be seen, with an almost linear release of approximately 50% by weight being seen after 96 hours for DNG1, DNG2 and DNG 5.

[0104] Dendritic nanogels were both able to encapsulate and deliver target peptides, as demonstrated by release studies monitored by confocal microscopy.

[0105] The present invention also provides a formulation comprising a dendritic nanogel carrier delivered in the form of a topical spray, gel, or pulmonary aerosol.

[0106] Example 1. General Synthesis Procedure of Dendritic Nanogels (DNG) Using DLDhb87 / 13 System

[0107] In a round-bottom flask, PEG20K-G3-allyl (200 mg, 8.75 μmol), trimethylolpropane tris(3-mercaptopropionate) (TMP-SH) (10, 6, 5, 4, 3 equivalents / allyl for DNG 1, DNG 2, DNG 3, DNG 4, DNG 5, respectively) and 2,2-dimethoxy-2-phenylacetophenone (DMPA) (10 wt%) were dissolved in DCM (4 mL). The solvent was slowly evaporated under reduced pressure to form a thin transparent film. Milli-Q water (40 mL) was added to the flask, and the flask was vortexed for 1 min and then immersed in an ultrasonic bath (35 kHz) for 15 min. Samples were taken for size and 1H-NMR analysis. The resulting colloidal dispersion was exposed to UV light for 60 minutes (Dosage = 1526 J / mm2) (UVP Blak-Ray UV bench lamp, Part Number (P / N): 95-00127-20M, 665 nm, 230 V, 50 Hz) under constant stirring. Samples were taken for size and 1H-NMR analysis. Mercaptopropionic acid (30, 50, 55, 60, 65 equivalents / allyl for DNG 1, DNG 2, DNG 3, DNG 4, DNG 5, respectively) and DMPA (10 wt %) dissolved in 2 mL THF were added. The sample was vortexed for 1 minute, immersed in an ultrasonic bath (35 kHz) for 15 minutes, and then exposed to UV light for 60 minutes (dosage = 1526 J / mm2) (UVP Blak-Ray UV bench lamp, P / N: 95-00127-20M, 665 nm, 230 V, 50 Hz) under constant stirring. Samples were taken for size and 1H-NMR analysis (size: 190 nm, conversion of allyl groups: (100 mol%)). The liquid was poured into a dialysis membrane and dialyzed with THF:H2O (2:3), (1:3) and then with solvent exchange of water at uniform intervals: 1, 1, 1, 2, 3, 15, 1 hour. The slightly turbid liquid obtained was freeze-dried to obtain the product (200 mg) as a fluffy cloudy solid.

[0108] Example 2. General Synthesis of MM-PEGXK-G3-OH (LD) and PEGXK-G3-OH (DLD)

[0109] Referring to the following publication by Ihre et al., different mPEG (Mw = 5000 g / mol, 10000 g / mol) and PEG (Mw = 10000 g / mol and 20000 g / mol) were used to produce MM-PEG5K-G3-OH, MM-PEG10K-G3-OH, PEG10K-G3-OH and PEG20K-G3-OH, respectively.

[0110] Example 3. General Synthesis of PEGXK-(hb)G3-OH(DLDhb)

[0111] The synthesis is based on the polycondensation reaction between PEG and Bis-MPA. PEG was added to a two-necked round bottom flask equipped with an argon inlet, a magnetic stirrer and a distillation apparatus and heated to 130°C. Every sixty minutes, an amount of bis-MPA corresponding to an increase of 1 generation of the dendrimer was added together with pTSA (bis-MPA added based on wt% pTSA; 1.5 wt% PEG2K, 5 wt% PEG6K and 5 wt% PEG20K). During the addition of bis-MPA, argon was flushed through the reaction vessel. When the desired generation was reached, an additional hour of argon flushing was applied and then vacuum was induced in the reaction vessel for 18 hours. The resin was extracted from the reaction vessel by dissolving in DCM and precipitating twice in diethyl ether in succession and then drying under high vacuum. According to the same reaction scheme, the second to seventh generations (G2-7) were synthesized for two different PEGs (Mw = 10,000 g / mol and 20,000 g / mol) used to make PEG10K-(hb)G3-OH and PEG20K-(hb)G3-OH, respectively (refer to Andrén et al. A1).

[0112] Example 4. General Properties of MM-PEGXK-G3-allyl, PEGXK-G3-allyl and PEGXK-(hb)G3-allyl synthesis

[0113] In a round-bottom flask equipped with a magnetic stirrer, the amphiphile was dissolved in pyridine (3 equivalents / OH) and DCM (10 ml). DMAP (0,2 equivalents / OH) was added and the reaction was cooled to 0 ° C using an ice bath. 4-pentanoic anhydride (1,2 equivalents / OH) dissolved in 5 mL DCM was slowly added over a 30 minute period. The reaction was allowed to proceed overnight and progress was monitored by 13C-NMR by confirming the presence of anhydride peaks at 170.2 ppm. The crude reactant was precipitated in ether (1 L), a white powder was collected, redissolved in DCM, and reprecipitated in cold ether (1 L). The product was collected as a white powder.

[0114] Example 5. Complete conversion of allyl groups in dendritic nanogel carriers

[0115] To ensure complete conversion of the remaining allyl groups, freeze-drying of DNG2 was performed and the presence of allyl groups was investigated by NMR spectroscopy. Fig.10 In (right), a spectrum can be seen where the signals associated with the allyl groups disappear completely after functionalization, indicating complete conversion to the carboxyl interior. Due to the formation of a core-shell structure, some degree of shielding of the desired structure can be expected, resulting in a slight underestimation of the amount of allyl groups (see Fig. 9 ). The cross-linking step can be performed as described above and results in different cross-linking rates as shown in Table 1.

[0116] The stability and appearance of DNG2 at different pH values ​​were investigated. At pH 4, a small pH-dependent shrinkage of DNG2 can be seen. This indication that the interior is indeed anionic can be seen as an effect of changes in the external pH, Fig.11 .

[0117] The stability of DNG has been evaluated using DLS, recording the size and polydispersity index (PDI) of the system stored in milli-Q water at room temperature after dilution in milli-Q water. Fig.12 The DNG 5 with the lowest crosslinking density showed a certain degree of instability, where after 150 days no spectra with satisfactory results could be recorded any more. The remaining DNGs appeared to be stable, even after almost 300 days of storage at room temperature.

[0118] DNG is essentially non-toxic, and the following MTT assay was performed to evaluate the toxicity of DNG 1, DNG 2, and DNG 3 that were modified to show anionic interiors, e.g. Fig.13 shown.

[0119] The subject matter of the invention is susceptible of numerous modifications and variations without departing from the inventive concept as expressed in the appended claims.

[0120] All the above details may also be replaced by other technically equivalent elements, and the materials may differ according to individual requirements, without departing from the scope of protection of the present invention.

[0121] Although the present invention has been described with particular reference to the accompanying drawings, the reference numerals used in the description and claims are intended to improve the intelligibility of the present invention and do not represent any limitation on the scope of protection claimed.

[0122] Different nanogels were prepared according to the method disclosed in Example 1.

[0123]

[0124]

[0125] Example 7

[0126] Fig.16 : Doxorubicin (DOX)-loaded DNG exhibited similar or improved anticancer efficacy compared with free DOX.

[0127] Fig.17:(ab) DOX (red) loaded in DNG can be delivered to 3D tumor models and distributed in both the nucleus (blue) and cytoplasm (green). And (c) Pure DNG labeled with blue fluorescent dye can also be taken up by 3D tumors. Combined with (ac), we know that DNG can be taken up by 3D tumors and deliver drugs to 3D tumors.

Claims

1. A nanogel comprising individual and / or interconnected nanoparticles having a core and a shell; wherein the nanoparticle comprises a self-assembled dendrimer having a dendritic linear dendrimer (DLD) scaffold architecture, the self-assembled dendrimer having a dendritic hydrophobic segment and at least one linear hydrophilic segment, wherein the branching degree of the hydrophobic segment is less than 1; wherein the core of the nanoparticle comprises a hydrophobic segment, and the shell of the nanoparticle comprises a hydrophilic segment; wherein the hydrophilic segment comprises polyethylene glycol (PEG) having a molecular weight ranging from 5,000 g / mol to 20,000 g / mol, and the hydrophobic segment is a second to fourth generation dendritic 2,2-bis(hydroxymethyl)propionic acid (bis-MPA) modified with allyl groups; wherein the core of the nanoparticle is anionic, cationic, hydrophilic and / or hydrophobic; and The hydrophobic segments are cross-linked via the allyl groups.

2. The nanogel according to claim 1, wherein 70-90% of the total molecular weight of the dendritic polymer is the hydrophilic segment and 10-30% is the hydrophobic segment.

3. The nanogel according to claim 2, wherein the relative percentage of the dendritic hydrophilic segments is 85-90 wt%, and the relative percentage of the hydrophobic segments is 10-15 wt%.

4. The nanogel according to claim 3, wherein the relative percentage of dendritic hydrophilic segments is 87 wt%, and the relative percentage of hydrophobic segments is 13 wt%.

5. The nanogel according to claim 1, wherein the cross-linking of the hydrophobic segment thioether is obtained by thiol-ene reaction.

6. The nanogel according to claim 1, comprising a fluorescent tag to provide traceability.

7. The nanogel according to claim 1, wherein the anionic core or cationic core is obtained by cross-linking the nanogel with mercaptopropionic acid or cysteamine and difunctional thiol or trifunctional thiol, respectively.

8. The nanogel according to claim 1, wherein the nanoparticles encapsulate cationic molecules selected from the group consisting of doxorubicin, cisplatin, gemcitabine, erlotinib, fluorouracil, mitoxantrone, irinotecan, idarubicin, triptolide, and paclitaxel.

9. The nanogel according to claim 1, wherein the nanoparticles encapsulate cationic molecules, wherein the cationic molecules are selected from the group consisting of cationic peptides, cationic proteins, cationic antigens and cationic synthetic molecules.

10. The nanogel according to claim 1, wherein the nanoparticles encapsulate anionic molecules selected from the group consisting of SI-RNA, anionic peptides, anionic proteins, anionic antigens and anionic synthetic molecules.

11. The nanogel according to claim 10, wherein the anionic synthetic molecules are diclofenac, salicylic acid and ibuprofenic acid.

12. The nanogel according to claim 1, wherein the allyl group is a C3-C6 allyl group.

13. The nanogel according to claim 12, wherein the allyl group is a C5 allyl group.

14. The nanogel of claim 1, wherein the nanogel is cross-linked using mercaptopropionic acid, cysteamine, or difunctional thiol or trifunctional thiol.

15. The nanogel according to any one of claims 1 to 14, wherein the molecular weight of the PEG is 5,000 g / mol to 10,000 g / mol.

16. A pharmaceutical composition comprising the nanogel according to any one of claims 1 to 15 for local drug delivery.

17. A pharmaceutical composition comprising the nanogel according to any one of claims 1 to 15 for use in treating an infection selected from the group consisting of skin infection, burn wound and lung infection.

18. The pharmaceutical composition according to claim 16 or 17, wherein the concentration of the nanogel is 3-6 mg / ml.

19. The pharmaceutical composition according to claim 18, wherein the concentration of the nanogel is 5 mg / ml.

20. A method for preparing a nanogel according to any one of claims 1 to 15, comprising the following steps: - Produce hydrophobic segments and linear hydrophilic segments; -Self-assembly of hydrophobic segments and linear hydrophilic segments into hybrid dendritic material scaffolds in the form of self-assembled core-shell nanoparticles; - Cross-linking of the nanoscale assembled scaffolds on available allyl groups to obtain nanogels; - Optionally post-functionalizing the nanogel to introduce desired functionality.

21. The method of claim 20, wherein the method comprises post-functionalizing the nanogel to introduce anionic, cationic or hydrophobic moieties.

22. An aqueous composition comprising the nanogel according to any one of claims 1 to 15, wherein the aqueous composition comprises 0.1-99.9 wt% of the nanogel.